Rising inequality and the politics of redistribution in affluent countries - Lane Kenworthy; Jonas Pontusson (Luxembourg Income Study (LIS), 2005)
Inequality has been an increasingly prominent object of study among comparativists. We use data from the Luxembourg Income Study to examine household market inequality, redistribution, and the relationship between market inequality and redistribution in affluent OECD countries in the 1980s and 1990s. We observe sizeable increases in market household inequality in most countries. This development appears to have been driven largely, though not exclusively, by changes in employment: in countries with better employment performance, lowearning households benefited relative to high-earning ones; in nations with poor employment performance, low-earning households fared worse. In contrast to widespread rhetoric about the decline of the welfare state, redistribution increased in most countries during this period, as existing social-welfare programs compensated for the rise in market inequality. They did so in proportion to the degree of increase in inequality, producing a very strong positive association between changes in market inequality and changes in redistribution. We discuss the relevance of Meltzer and Richard's median-voter theory and power resources theory for understanding cross-country differences and over-time changes in the extent of compensatory redistribution.
Keywords: 330; Einkommensverteilung; Öffentliche Sozialleistungen; Gini-Koeffizient; Europa; Australien; Nordamerika